Trans-Spinal Direct Current Stimulation in Spasticity: A Literature Mini-Review - Estudillo-Guerra, Maria A.; Mesia-Toledo, Ines; Rogel, Noga; Yaghoubi, Nader; Ahmed, Zaghloul; Black-Schaffer, Randie; Morales-Quezada, Leon (Frontiers in Stroke, 2022)
Spasticity is common after a stroke and has a negative impact on functional and quality-of-life measures. There is an unmet medical need to provide safe and effective treatment using non-pharmacological approaches. Trans-spinal direct current stimulation (tsDCS) is an emerging modality for non-invasive neuromodulation that induces reduction of spinal excitability leading to a decrease in spasticity. We describe current treatment options for spasticity, including a literature review about the use of tsDCS in patients with spasticity. We found four clinical studies that used tsDCS to treat spasticity for different neurological conditions including hereditary spastic paraplegia, upper extremity spasticity following stroke, multiple sclerosis, and incomplete chronic spinal cord injury. Spasticity was the primary outcome in three of the studies and a secondary outcome in the final study. The three studies that addressed spasticity as the primary outcome found that active tsDCS decreased spasticity compared to sham. These studies suggest that tsDCS can modulate spinal motor and sensory spinal pathways through the use of specific electrode montages and stimulation parameters. This therapy can improve motor functions and may represent a viable treatment option for spasticity.